Coordinated IgG2 and IgE responses as a marker of allergen immunotherapy efficacy. Issue 4 (6th October 2021) - Bordas‐Le Floch, Véronique; Berjont, Nathalie; Batard, Thierry; Varese, Nirupama; O'Hehir, Robyn E.; Canonica, Walter G; van Zelm, Menno C.; Mascarell, Laurent
Abstract: Background: IgG2 responses are associated with repeated antigen exposure and display highly mutated variable domains. A recent study highlighted a role of IgG2+ memory B cells and allergen‐specific IgG2 levels after a 3rd consecutive pre‐seasonal sublingual allergen immunotherapy (AIT) with grass pollen tablet. Herein, we aim to explore changes in allergen‐specific IgG2 in individuals undergoing house dust mite immunotherapy (HDM‐AIT) and explore whether the interrelationship with other humoral responses (i.e., IgG4 and IgE) may discriminate between high and low responders. Methods: Levels of serum Dermatophagoides pteronyssinus and Dermatophagoides farinae ‐specific IgG2, IgG4, and IgE antibodies were measured by ELISA or ImmunoCap in a sub‐group of individuals enrolled in a randomized, double‐blind, placebo‐controlled, sublingual AIT study evaluating the safety and efficacy of a 300 IR HDM tablet. Results: After 1‐year sublingual AIT, HDM‐specific serum IgG2 responses increase mostly in high versus low responders and are distinctive according to the clinical benefit. Higher correlation between HDM‐specific IgG2, IgE, and/or IgG4 responses is seen in subjects benefiting the most from HDM‐AIT as indicated by changes in Average Total Combined Scores. More strikingly, statistically significant correlation between HDM‐specific IgG2 and IgE responses is only observed in individuals stratified as high responders. Conclusions: We provide evidence for coordinated serum immune responses upon AIT in HDM‐allergic subjects exhibiting high clinical benefit when compared with low responders. Assessing HDM‐specific IgE, IgG2, and IgG4 in serum could be used as follow‐up combined markers to support decision as to AIT continuation and/or adaptation. Abstract : This study assesses humoral responses in HDM‐allergic individuals beforeand after 1‐year HDM tablet sublingual AIT. Individuals suffering from HDM allergy exhibit an increase in serum HDM‐specific IgG2 following 1‐year AIT. Correlations observed between changes in IgG2 and IgE antibody levels highlight coordinated humoral responses only in high responders during AIT. Abbreviations: AIT, allergen immunotherapy; HDM, house dust mite; IR, index of reactivity